Schools that Don’t Close: Possible Places and Spaces for Progressive Teaching, Learning, and Research - Harris, Carol Elizabeth (Alberta Journal of Educational Research, 2015)
Small schools and their communities contribute to an important, though threatened, knowledge base. The threat adheres in underlying technologies (conceptual and material) that propel the capitalistic world towards the rationalization of all aspects of human activity. In education, this appears in the consolidation of small schools and ever larger units of organization. From three studies of Newfoundland coastal communities, I describe schools that were deemed to be “necessarily existing.” Because of their isolated location, students from the schools could not be transported to larger centres. While reporting both positive and negative features of actual small, rural schools, I argue against hasty school closures and point, instead, to rural school and community opportunities for “place, voice, and space-based” teaching, learning, and research. Small, rural schools can be pivotal in leading Canadian education from its deeply rooted, market-based ideology to progressive and socially relevant practices that embrace lifelong learning, community involvement, and ecological awareness and action. Les petites écoles et leurs communautés nous fournissent l’occasion d’augmenter notre base de connaissances, mais leur contribution est menacée. La menace provient de technologies sous-jacentes qui propulsent le monde capitaliste vers la rationalisation de tous les aspects de l’activité humaine. Dans le domaine de l’éducation, ce phénomène se manifeste par la consolidation des petites écoles et des unités administratives toujours plus grandes. À partir de trois études portant sur les communautés côtières à Terre-Neuve, je décris trois écoles désignées comme « obligatoirement existantes ». Compte tenu de leur isolement, les élèves des écoles ne pouvaient être transportés vers de plus grands centres. Je présente les aspects positifs et négatifs des petites écoles rurales actuelles, tout en militant contre les fermetures hâtives et en soulignant que les écoles et les communautés rurales sont des lieux qui représentent des occasions d’enseignement, d’apprentissage et de recherche qui reflètent « le lieu, la voix et l’emplacement ». Les petites écoles rurales peuvent jouer un rôle clé pour éloigner le système éducatif canadien de son idéologie de marché bien ancrée et le diriger vers des pratiques progressives et pertinentes sur le plan social qui endossent l’éducation permanente, l’implication communautaire, et une conscience et une action écologiques.